Signal quality monitoring aspects in GNSS signals affected by evil waveforms - Sousa, Fernando (2022)
Evil waveforms (EWF) are anomalies in the GNSS transmitted signals that can degrade significantly the accuracy of the PVT solution. The cross-correlation function of the incoming signal disturbed by EWF distortion and the locally-generated code signal is obtained analytically for threat models TM-A, TM-B and TM-C. These results are useful to evaluate efficiently the performance of EWF detectors, namely the detectability and hazard regions.